Selective vulnerability of the suprachiasmatic nucleus in progressive Alzheimer’s Disease: A human postmortem study using spatial in‐situ proteomics - Son, Gowoon; Mladinov, Mihovil; Pereira, Felipe Luiz; Tu, Chia‐Ling; Li, Song Hua; Suemoto, Claudia Kimie; Leite, Renata Elaine Paraizo; Paes, Vitor Ribeiro; Pasquallucci, Carlos Augusto; Jacob‐Filho, Wilson; Spina, Salvatore; Seeley, William W.; et al. (Alzheimer's & dementia, 2023)
Background Alzheimer’s Disease (AD) patients commonly experience sleep/wake (S/W) disturbances, such as sleep fragmentation and excessive daytime sleepiness. The S/W cycle is controlled by a complex system regulated by a master regulator, the suprachiasmatic nucleus (SCN) that controls wake‐ and sleep‐promoting nuclei. Despite its importance in orchestrating sleep architecture, little is known about the molecular changes that occur in the SCN during the progression of AD and how these changes contribute to S/W disturbances. Method We used postmortem brain tissue of 10 controls without AD pathology and 32 subjects with progressive AD stages. Our approach included quantitative neuropathological assessments of AVP and VIP‐expressing neurons in SCN and its adjacent hypothalamic region, the supraoptic nucleus (SON). We also used an in‐situ cell‐specific spatial proteomics platform [GeoMx Digital Spatial Profiling (DSP)] to probe levels of different pathological tau species and proteins commonly dysregulated in AD. Result Preliminary findings reveal a significant decrease in SCN volume (∼75%) (Fig.1) and a loss of ∼58% AVP neurons and ∼41% VIP neurons in Braak stage (Braak) VI compared to Braak 0. The DSP results indicate that both neurons in the SCN have twice the burden of p‐tau levels as the SON (Fig.2‐right), and neurofibrillary tanglesAdditionally, SCN shows an increase in proteins associated with glia and immune responses (Fig.2‐left). Furthermore, an increase in microglial proteins is observed in the SCN in Braak I (Fig.3‐left). In contrast, the SON displays a milder pattern of protein dysregulation in Braak I (Fig.3‐right), consistent with its lower tau expression observed in histology and DSP. Conclusion SCN is vulnerable to AD pathology even in Braak I, which is characterized by volume loss, increased immune response protein dysregulation, and later neuronal loss, as well as p‐tau pathology. This pattern supports the idea that the SCN plays a role in S/W disturbances observed from early AD stages. Interestingly, its neighboring nucleus, SON, which also has AVP neurons, remained spared, providing opportunities for studies investigating factors related to selective vulnerability. Ongoing studies are addressing changes in the SCN and SON in intermediate AD stages.